PERAN PENTING BIMBINGAN KELOMPOK DI SEKOLAH DASAR - Azzahra, Fauziah; Salo, Alimuddin; Ferdin; Nengsih, Luluk Wahyu (Sindoro: Cendikia Pendidikan, 2024)
Group tutoring is one of the important guidance and counseling services in elementary schools. This service has an important role in helping students develop themselves optimally, both in terms of academic, social, emotional and moral. Group tutoring in elementary school can help students develop their potential, improve social skills, build character, and overcome problems. Group tutoring in elementary school can be implemented using various methods which must be adapted to the needs and characteristics of students. Group guidance in elementary school must be carried out in an ongoing and structured manner. The important role of guidance and counseling teachers and class teachers is very important in the successful implementation of group guidance in elementary schools.